The Decision to Expropriate - Mejorada Chauca, Martín (2014)
Property rights represent the maximum power over a good. This is the essence of that right. However, beyond that base is possible a greater or smaller degree of limitation, according to the legal system and the prevailing ideology in the Constitution. the author argues that it is essential to tie the concept to the prevailing economic system, because in a closed economy we can tolerate greater limitations on this right that in an open economy. Peru, certainly, changed its model to an open economy in 1993, when it limited the possibility of expropriation. However, this does not ensure eradication of different readings under the veil of a social interest, so the expropriation is only justified for the author if“its realization will positively affect to the entire society”.